Tastes, Castes, and Culture : The Influence of Society on Preferences - Fehr, Ernst; Hoff, Karla (2012)
Economists have traditionally treated preferences as exogenously given. Preferences are assumed to be influenced by neither beliefs nor the constraints people face. As a consequence, changes in behaviour are explained exclusively in terms of changes in the set of feasible alternatives. Here the authors argue that the opposition to explaining behavioural changes in terms of preference changes is ill-founded, that the psychological properties of preferences render them susceptible to direct social influences, and that the impact of "society" on preferences is likely to have important economic and social consequences.